PENINGKATAN MINAT BELAJAR MATEMATIKA MELALUI PEMANFAATAN PAPAN PERKALIAN PADA SISWA SEKOLAH DASAR NEGERI 16/VI MUARA SIAU I - Permata Sari, Caca; Ahmad , Saidah; Nofriadi, Nanang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by students’ low interest in learning mathematics, particularly the topic of integer multiplication, in the fourth grade at SD Negeri 16/VI Muara Siau I. The learning process is still dominated by lecture-based methods and does not yet utilize engaging learning media, resulting in students being less active, less enthusiastic, and experiencing difficulties in understanding the concept of multiplication. This study aims to describe the use of multiplication boards as a learning medium and to determine the increase in students’ interest in learning after using this medium. This study is a Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The research subjects were 14 fourth-grade students at SD Negeri 16/VI Muara Siau I. Data collection methods included observation, questionnaires, interviews, and documentation. The data were analyzed using descriptive quantitative and qualitative methods. The results of the study indicate that the use of multiplication boards is carried out through the following steps: the teacher prepares the material, communicates the learning objectives, explains the concept of multiplication as repeated addition, demonstrates the use of the multiplication board, provides students with the opportunity to use the material directly, guides students during the learning process, and provides practice exercises and assessments. The use of multiplication boards as a teaching aid was able to improve the quality of the learning process and students’ interest in learning. This was evident from the results of the learning interest questionnaire, which showed an increase from 59% in Cycle I to 80% in Cycle II. Teacher activity also increased from 78% to 93%, while student activity increased from 57% to 81%. Thus, it can be concluded that the use of multiplication boards as a learning medium effectively increases students’ interest in learning mathematics, specifically the multiplication of whole numbers, in Grade 4 at SD Negeri 16/VI Muara Siau I.